New International Monetary Arrangements and the Exchange Rate - Tommaso Monacelli (Oesterreichische Nationalbank (OeNB), 2001)
I show how to implement in a simple manner the comparison of alternative monetary policy rules in a two- country model of the new generation. These rules are: Full Price Stability, Taylor, Fixed and Managed Exchange Rates. I find, first, that the exchange rate dynamic is non-stationary unless some form of management is undertaken by the respective monetary authorities of the two countries. However, eliminating the excess volatility of the exchange rate does not significantly alter the overall macroeconomic volatility. Second, a floating exchange rate regime based on a Taylor-type rule seems to better approximate the full price stability benchmark, but at the cost of boosting interest rate volatility. In this respect limiting exchange rate flexibility is desirable. Finally, in all cases the model delivers positive cross-country correlation of interest rates but negative cross-country correlation of output.
Keywords: E52; F41; 330; monetary policy rules; exchange rate